2009
DOI: 10.1166/jnn.2009.049
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Cell Adhesion Molecules in Mice's Lung After Administration of Meso-2,3-Dimercaptosuccinic Acid-Coated Maghemite Nanoparticles

Abstract: We studied the expression pattern of cell adhesion molecules associated to transendothelial migration of leukocytes in different lung's vascular compartments after administration of a magnetic fluid sample containing maghemite nanoparticles surface-coated with meso-2,3-dimercaptosuccinic acid. The analyses were conducted in mice 4 and 12 h after endovenous administration of the magnetic fluid in control mice. Firstly, the migratory activity of leukocytes after magnetic fluid surface-coated with meso-2,3-dimerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In this case, both LFA-1 and VLA-4 could play a functional role in the process of transendothelial migration of monocytes induced by MNPs-DMSA. Supporting this perspective, we have previously shown that MNPs-DMSA modulate the expression pattern of LFA-1 on leukocytes located in the vascular compartment of the lung [6]. Conversely, the absence of a significant change in the mRNA expression of VCAM-1 (Fig.…”
Section: Cell Adhesion/emigration Pathwaysupporting
confidence: 54%
See 4 more Smart Citations
“…In this case, both LFA-1 and VLA-4 could play a functional role in the process of transendothelial migration of monocytes induced by MNPs-DMSA. Supporting this perspective, we have previously shown that MNPs-DMSA modulate the expression pattern of LFA-1 on leukocytes located in the vascular compartment of the lung [6]. Conversely, the absence of a significant change in the mRNA expression of VCAM-1 (Fig.…”
Section: Cell Adhesion/emigration Pathwaysupporting
confidence: 54%
“…While MNPs-DMSA has been shown to cause transendothelial migration of leukocytes into the lung [4][5][6], the time course of this process is still unclear. In the present study, we detected a timedependent increase in the number of leukocytes in bronchoalveolar lavage fluid within the first 12 h after administration of MNPs-DMSA as compared to controls (P < 0.05; Fig.…”
Section: Migration Activitymentioning
confidence: 99%
See 3 more Smart Citations